Factors Influencing Olfactory Perception of Selected Off-flavourcausing Compounds in Red Wine - A Review - McKay, M.; Buica, A. (South African Journal of Enology and Viticulture, 2020)
Extensive work on the chemical aspects of off-flavour in wine has been carried out by international researchers, but not as many studies focus on the organoleptic effects. This literature review therefore has a focus on the status of the sensory aspects of compounds associated with specific off-flavours in red wine, viz. three volatile phenols, as well as 2-isobutyl-3-methoxypyrazine and 2,4,6-trichloranisole. The review discusses sources and effects of the selected compounds in red wine, and what previous workers have found pertaining to the mechanisms of the odour perception of aroma compounds, odour detection thresholds, and issues relating to the effects of the matrix. It also considers the factors that have been found to cause differences in olfactory perceptions between panellists/judges, and covers some of the work that has been carried out in characterising perceptual interactions between compounds in wine. Gaps that exist in the current literature are highlighted.